Falls and associated risk factors in a sample of old age population in Egyptian community - El Sayed, Abd El Hamied Ibrahim; Said, Mohamed T.; Mohsen, Omnia; Abozied, Aziza M.; Salama, Mohamed (Frontiers in Public Health, 2023)
Introduction Falling is a major health problem among old age persons and are the sixth cause of mortality and morbidity among them. Assessing the prevalence of falls among elderly in an Egyptian community and investigating its associated risk factors using the Arabic translation of the SHARE-Questionnaire. Subjects and methods This cross-sectional analytic study was a part of the pilot for AL-SEHA project. It included 289 old age people (50+ years age) residing in the study areas. The main project data were collected using the Arabic translation of the SHARE (Survey of Health, Aging, and Retirement in Europe) questionnaire. The original project data were collected by investigators from five universities, then uploaded to the internet server domain of the American University in Cairo (AUC) Social Research Center. Results The prevalence of falls was 11.07% (95% CI: 7.95–15.21). Falls were significantly more among 70 years or older (p < 0.001), unemployed or housewives (p = 0.026), have a family caregiver (p = 0.022), and home facilities for disability (p = 0.015). They had significantly higher rates of ischemic heart disease, hypertension, dyslipidemia, stroke, and diabetes mellitus. The most frequently reported problems were the fear of fall and dizziness (62.5%). The multivariate analysis identified the history of stroke and diabetes mellitus, the fear of fall and dizziness, and the total number of health problems and the score of difficulty in performing physical activities as significant independent predictors of fall occurrence. The history of stroke was the strongest risk factor (OR 33.49, CI: 3.45–325.40). Discussion and recommendations The prevalence of falls among old age persons in the studied community is not alarmingly high. It is highest among stroke patients. Community interventions and rehabilitation programs are recommended to train and educate old age people, especially those at risk such as stroke and diabetic patients, and those with dizziness to improve their physical fitness and reduce the fear of fall among them.